Spatio-temporal variability in fatty acid trophic biomarkers in stomach contents and muscle of Iberian sardine (Sardina pilchardus) and its relationship with spawning - Garrido, Susana (2013)
Temporal variation in the fatty acid (FA) composition of stomach contents of Iberian sardines was compared to the relative contribution to dietary carbon made by different prey types for Wsh from two areas of Portugal. The effect of the FA content of the diet on sardine muscle FA composition was also studied, aiming at (1)analysing if FA biomarkers can be used as a complementary technique for the study of sardine diet and (2) to relate spatial and temporal variations of prey FA content with sardine condition and reproduction. Significant spatial differences in the FA composition of sardine diet occurred with concentrations of n-3 polyunsaturated FA, namely eicosapentaenoic acid [EPA, 20:5n-3] and linolenic acid 18:3n-3, being signifcantly higher in the diet of sardines from the west coast, whilst the diet of sardines from the south coast was richer in monounsaturated fatty acids (MUFA), namely the carnivory biomarker oleic acid 18:1n-9. These results are in agreement with the higher contribution made by diatoms and dinoflagellates to the diet of sardines of the west coast. Spatial variation in sardine dietary FA was also detected in their muscle composition, specifically for EPA, and the eicosapentaenoic/docosahexaenoic acid and (n-3)/(n-6) ratios, which were higher in sardines from the west coast. No difference in FA composition was detected between sexes, and the seasonal variability in sardine total FA concentration was primarily related to the seasonality of spawning. Sardines accumulate high concentrations of FAs during the resting stage of reproduction when the feeding intensity is similar or lower to that observed during the spawning season. Additionally, sardines show a high selective retention of MUFA and polyunsaturated FA (PUFA) throughout the year except at the beginning of the spawning season, when these FAs are largely invested in the formation of the gonads. Therefore, temporal and regional diVerences of prey environments are strong enough to be reflected in fish body composition, namely on the accumulation of essential FAs, which can have a strong impact on reproduction success for this species.